Sexual harassment at the university: Evaluation of a preventive awareness workshop - Blahopoulou, Joanna; Ortiz-Bonnin, Silvia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The goal of this article is to present the design of and evaluate an awareness workshop against sexual harassment. A total of 286 students (224 women and 62 men) from different studies at the University of the Balearic Islands participated in the workshop. The participants showed high satisfaction with the workshop; 197 even gave the maximum score in all 9 items of the evaluation questionnaire. These results encourage the promotion of its application in other studies and, also within the training framework of the university staff members.